Model selection may not be a mandatory step for phylogeny reconstruction - Shiran Abadi (Nature Portfolio, 2019)
Model selection is a time-intensive step of molecular phylogenetic analysis. Here, Abadi, Azouri and colleagues show that all model selection criteria lead to similar inferences, and that for topology and ancestral sequence reconstruction, using the GTR+I+G model is as accurate.